Methodological resources of the new epistemology of sciences - Онопрієнко, В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. Social epistemology of science is a modern field of research that is actively developing in the world, producing new approaches and generating heated debate. It did not arise from scratch and is a synthesis of several philosophical and special scientific concepts. In the post-Soviet space, this area of research is effectively and on an original conceptual basis developed at the Institute of Philosophy of the Russian Academy of Sciences, where a new understanding of cognition as creativity has formed. The aim and tasks are to show the advantages of modern social epistemology of science, expanding the horizon of philosophy and methodology of science, to convince researchers to use a new arsenal of cognitive tools. Research methods used in the article are directly connected with the new concept of cognition: cognition is understood as a process that accompanies the activities and communication of people and performs the function of providing them in an ideal way. Creative knowledge gives rise to virtual worlds, creates the prerequisites for the creation and existence of cultural objects in general. Modern interest in virtualism is associated with methods of expanding the horizon of consciousness, creating the prerequisites for generating any cultural object. Research results. Cognition is a philosophical category that describes the process of constructing ideal plans for activity and communication, creating symbolic systems. Cognition is an independent reality that permeates all aspects of the human world and can only be distinguished from it in abstraction. Cognition deals with the content of collective activity and communication, which for their organization need ideal, i.e. possible, trial, approximate, variable models. The dynamics of the generation of knowledge is vectorial in nature, associated with a research, search setting to expand the scope of ideal constructs. The function of cognition is to superimpose a network of signs on the world - scientific formulas, moral norms, artistic images, magic symbols that allow a person to organize his being in the world and structure his psyche in such a way as to give it mobility and variability, thereby providing the possibility of activity and communication. The main feature of human cognition, unlike the analogous psyche of animals, is constructiveness. Discussion. Cognition is not copying of cognizable reality; it is an introduction of meaning into reality, the creation of ideal models that allow directing activity and communication and systematizing acts of consciousness. Conclusion. The article illustrates the innovativeness of the new approach in the framework of social epistemology, providing intellectual evidence for it, using examples of new categories.